Achieving seamless and scalable ethernet networks using ethernet over SONET - Jape, Milind (2008)
This dissertation focuses on a new layer 2 mapping technology "Ethernet Over SONET", in which virtual concatenation and link capacity adjustment scheme have given the SONET a new lease of life around the world by extending Ethernet over Metropolitan area Network (MAN) and Wide Area Network (WAN).